Pandemic funerals in Norway: Hartmut Rosa’s resonance as a sensitizing concept - Schuerhoff, Carsten (Approaching Religion, 2023)
During the Covid-19 pandemic, funerals have been conducted consistently in Norway, but, of course, the ceremonies were subject to rules and regulations, while digitization was on the increase. Against the background of already ongoing discussions, both in contexts related to the Church of Norway and in practical-theological discourses, this article analyses scenes and excerpts from interviews conducted in 2021 and asks: What does the sociologist Hartmut Rosa’s concept of resonance convey in the pandemic situation? – This concept aims at a mode of relating that empowers fulfilling, resonant relationships between subjects and between subject and world; the aim here is to bring it into play as a sensitizing concept, in a situation of supposedly increased distance and unaffectedness between people. The article discusses where the concept conveys the need for stable frameworks, and where it conveys the need for ongoing work with an ecclesiastical-theological self-understanding in the field of church funerals.